Tracing Speech Acts Through Text and Genre: Directives and Commissives in Queen Elizabeth I's Political Speeches and in Shakespeare's Henry V - Montini, Donatella (Status Quaestionis, 2014)
The essay investigates some stylistic and pragmatic variations across two genres and text-types pertaining to political oratory in Early Modern England. The speaker in question is the Renaissance monarch who, as many studies have shown from a cultural perspective, appropriates the forms of stage performance and, by manipulating them, acts his power and performs a relationship with his subjects. In this respect my study proposes to analyse and compare some aspects of non-literary and literary texts, Queen Elizabeth I’s parliamentary speeches and Shakespeare’s Henry V’s monologues, as text-types which share a strong persuasive and argumentative aim and are both speech-purposed. The working hypothesis of my case study is that, by drawing attention to two specific speech-acts, directives and commissives, the evaluation of the illocutionary force of their speeches will shed light also on some typical features of the political discourse of Early Modern England.